Diamond chemical vapor deposition nucleation and early growth stages - Liu, Huimin, 1961- (Noyes Publications, 1995)
This book presents a systematic review of the latest developments in diamond CVD processes, with emphasis on the nucleation and early growth stages of diamond CVD. The objective is to familiarize the reader with the scientific and engineering aspects of diamond CVD, and to provide experienced researchers, scientists, and engineers in academics and industry with the latest developments in this growing field.
Keywords: Chemical vapor deposition.; Diamonds, Artificial.; elektronické knihy; electronic books